Uncommon valor [videorecording (Blu-Ray)] - Gayton, Joe; Hackman, Gene; Ward, Fred, 1942-2022; Brown, Reb, 1948-; Cobb, Randall, 1950-; Stack, Robert, 1919-2003; Swayze, Patrick (Paramount Home Entertainment, 2020)
Ten years after his son goes missing-in-action during the Vietnam War, his Amertican father puts together a rescue mission with his son's old unit. Rumours are that there are still POWs in a camp in Laos.